Retorika Simbol Islam pada Akun Instagram Ridwan Kamil - Fathayatul Husna (Jurnal Komunikasi Global, 2018)
Ridwan Kamil as a mayor of Bandung is known as a successful leader to build his region. Most of his government programs were published through his Instagram account @ridwankamil. Besides, his Instagram images mostly contain Islamic symbols. This study aims to analyze the practice of rhetoric through the symbols of Islam on Instagram account @ridwankamil. This research used a qualitative content analysis based on rhetorical discourse theory from Aristotle. This theory is used to analyze three photos containing Islamic symbols on Instagram account of Ridwan Kamil. The results of this study indicated that each photo containing Islamic symbols showed him as an Islamic figure. This study concludes that social media not only plays an important role to strengthen social interaction but also advance political strategy.